System Dynamic Model for Lake’s Water Flow: A Case Of Situ Binong, Cikarang, West Java, Indonesia - Muchammad Chusnan Aprianto (Universitas Hasanuddin, 2018)
This study aims to develop a dynamic system model that describes the relationship ofwater, socio-economic, and water resources (lake size) sub-systems in Situ Binong. In addition,this study also aims to make predictions of water resources conditions (lake size) Situ Binong forthe next 5 years. The model is prepared using a dynamic system approach. The Situ Binong waterflow model is available water resources consisting of 3 sub-systems namely natural water flowsub-systems, socio-economic, and water resources Situ Binong. The result of the research showsthat the requirement of Situ Binong water resources every year is increasing so that the volume ofSitu Binong is decreasing. In addition, the volume of water resources Situ Binong influenced bysupply and demand. Supply comes from domestic waste and natural water flow such asprecipitation, infiltration and surface flow. While demand comes from WTP intake, irrigation, andevaporation.